Pengelolaan Konten Instagram BRI Regional Office Jakarta 3 Sebagai Media Informasi Publik - Fadhillah Amanda; Trie Damayanti (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
Digital banking products will be promoted and become educational material for the public through social media, especially Instagram. These digital products include BRIAPI, Ceria, and BRImo. The BRI RO Jakarta 3 social media team has not yet maximized the function of digital tools in supporting media monitoring activities on Instagram @bri_regionaljakarta3 because so far they have only relied on Instagram's analytical insight tools whose features can be said to be minimal. The aim of this research is to discuss in more depth the management of content on Instagram based on contributions made by authors and new findings in the field so that later it can be aligned with the function of publication activities via social media as a credible information medium for the public or BRI customers, especially for users who become a follower on Instagram @bri_regionaljakarta3. The method used is an exploratory study. Based on the results of observations that I found in the field, the use of Instagram is considered to be the main media that is effective in disseminating information related to BRI RO Jakarta 3 with the public.